Healing wounds, defeating biofilms: Lactiplantibacillus plantarum in tackling MRSA infections - Dubey, Ashish Kumar; Sharma, Mohini; Parul,; Raut, Sachin; Gupta, Pawan; Khatri, Neeraj (Frontiers in Microbiology, 2023)
Methicillin-resistant Staphylococcus aureus (MRSA) infections are noted hospital borne infections and are major contributing factor to global health concern of antimicrobial resistance due to the formation of biofilms. Probiotics are known to assist in healing of wound through immunomodulation and also possess anti-pathogen properties via competitive inhibition. The probiotic bacterium, Lactiplantibacillus plantarum MTCC 2621 and its cell free supernatant (Lp2621) has previously been reported to have antibacterial, excellent antioxidant and wound healing activity in in vitro and wounds contaminated with S. aureus in mice. In current study, we have evaluated its anti-MRSA, biofilm inhibition and eradication efficacy, immunomodulatory activity in THP-1 cells and wound healing potential in wounds contaminated with MRSA infection in mice. In agar well diffusion assay, Lp2621 showed anti-MRSA activity and revealed dose dependent inhibition and eradication of biofilm by crystal violet assay as well by Confocal Scanning Laser Microscopy (CLSM) analysis. Further, Lp2621 showed immunomodulatory activity at varied concentrations as measured by IL-6 and IL-10 gene expression in THP-1 cells. Similar findings were observed in serum samples of mice after treatment of excision wound contaminated with MRSA infection by Lp2621 gel as evident by expression of IL-6 (proinflammatory) and IL-10 (anti-inflammatory) cytokines. Overall, our results show that Lp2621 has potent anti-MRSA and antioxidant properties and can prevent and eliminate biofilm formation. It also showed promise when applied to mice with MRSA-infected wounds.